PERAN KORO-SENSEI SEBAGAI GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM: Analisis Naratif Film Assassination Classroom - Nabila Nur Amarina; Abdurrohim Abdurrohim (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study intends to investigate the role of Koro-sensei as an educator in the anime Assassination Classroom using a narrative analysis approach, and to interpret it through the lens of Islamic Religious Education (PAI). In the framework of Islamic education, in addition to being a transmitter of knowledge (mu’allim), teachers are also regarded as moral and spiritual mentor (murabbi). Despite being a fictional character, Koro-sensei demonstrates the qualities of an ideal teacher, such as exemplary behavior, compassion, individualized instruction, and a willingness to sacrifice for his students’ development. This qualitative study conducts a narrative analysis of all 47 episodes of the anime and is supported by a literature review on Islamic perspectives regarding the ideal educator. The findings indicate that Koro-sensei reflects key Islamic educational values, including trustworthiness (amanah), sincerity (ikhlas), patience (sabr), empathy (ta’aruf), and wise nurturing (tarbiyah bil hikmah). Moreover, the anime presents itself as a promising contextual learning tool for PAI, especially for the digital native generation. Therefore, this study contributes to the advancement of Islamic education models that are relevant, reflective, and creative by incorporating elements of popular culture.